Product of Serum Calcium and Phosphorus (Ca x Pi) as a Predictor of Cardiovascular Disease Risk in Patients with Chronic Kidney Disease - Bakhunchhen, Rojina; Dubey, Raju Kumar; Jayan, Archana; Shah, Santosh Kumar; Khatri, Prabin (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Most of the chronic kidney disease (CKD) patients develop cardiovascular disease (CVD) in their later stages. Various traditional CVD risk factors are highly prevalent in CKD but mortality of these patients cannot be fully justified by these CVD markers. So this study was designed to determine serum calcium and phosphorus product (Ca×Pi) to predict CVD risk in CKD patients. MATERIAL AND METHODS We followed the guidelines of NKF-KDOQI for CKD diagnosis and staging. Further the patients were classified into 3 different groups based on Ca×Pi product; <40 mg2/dl2 (group 1), 40-55 mg2/dl2 (group 2) and >55 mg2/dl2 (group 3). We then evaluated CVD risk by various traditional risk factors like age, BMI, BP, smoking history, dyslipidemia, previous history of CVD, LVH, arrhythmia, VHD, cardiomyopathy, and IHD. RESULTS: Higher level of Ca×Pi was associated with presence of LVH (32.30% in group 1, 31.42% in group 2 and 46.66% in group 3), Arrythemia (13.84% in group 1, 28.57% in group 2 and 46.67% in group 3), VHD (5.71% in group 2 and 10.00% in group 3), Cardiomyopathy (1.53% in group 1, 8.57% I group 2 and 6.66% in group 3), IHD (6.15% in group1, 11.42% in group 2 and 13.33% in group 3) and hypercholesterolemia, hypertriglyceridemia and increased LDLc. CONCLUSION: This study found that higher Ca×Pi increases with decline in glomerular filtration rate (GFR) and associated with CVD risks and CVD. So, this study raise a potential need to evaluate the level of calcium and phosphorus in all CKD patients and the level should be monitored more thoroughly to prevent CVD.